SUBSTITUTION OF LIVE FEED BY FORMUlATED DIET: EFFECT ON THE GROWTH AND SURVIVAl OF BETTA SPLENDENS (REGAN) FRY - Mandal, Sagar C; Kohli, M.P. S.; Sahu, N. P.; Prakash, C.; Chadha, N. K.; Munilkumar, S.; Das, Pronob (Journal of Indian Fisheries Association, 2009)
The present work evaluates the effectiveness of partial or total replacement of live feed(LF} (Tubifex) together with formulated diet (FD) for Betta splendens. Three hundred Bettasplendens fry of uniform size (mean weight 0.19Â±0.01g) were equally distributed in five treatmentgroups with three replicates in glass aquaria of 351itre capacity. Fishes were given diets at differentratio of LF and FD viz. T1(C}100% LF; T275% LF, 25% FD; T350% LF, 50% FD; T425% LF, 75% FD andT5100% FD and the experiment continued for 105 days. T2 group registered highest (P